The relationship between self-efficacy/resilience and the mental health status of hemodialysis nurses: multiple mediation effects of insomnia and fatigue - Zhang, Wen-Xuan; Ye, Xiao-Qing; Wen, Sui-Qin; Wang, Rao-Ping; Li, Ying-Hua (Frontiers in Psychology, 2025)
Background and purposeDue to the high frequency of hemodialysis treatment, hemodialysis nurses have to bear a lot of psychological pressure, which makes them more vulnerable to anxiety and depression. This study aims to explore the relationship between self-efficacy/resilience and the mental health status of hemodialysis nurses and mediating roles of insomnia and fatigue.MethodsA cross-sectional study was conducted in hemodialysis rooms/centers in Guangdong Province, China, including 1630 nurses aged between 18 and 59. Structural equation model (SEM) was used to explore the relationship between self-efficacy/resilience and the mental health status of hemodialysis nurses, as well as multiple mediation effects of insomnia and fatigue.ResultsThe results of multiple mediation effects analysis based on SEM suggested that the above-mentioned factors can directly affect the mental health status of hemodialysis nurses. Furthermore, insomnia and fatigue played multiple mediating roles in the pathway of self-efficacy/resilience and the mental health status of hemodialysis nurses.ConclusionThe specific demands of hemodialysis nursing bring various stressors that can negatively affect the mental health status of hemodialysis nurses, which makes them vulnerable to negative emotions. Therefore, finding ways to improve self-efficacy and resilience, and take care of sleep quality to reduce fatigue is essential to improve the mental health status of hemodialysis nurses.